First contribution to the description of reproductive structures of Nelsonia goldmani (Rodentia: Cricetidae) - León-Tapia, M. Ángel; Cervantes, Fernando A. (THERYA, 2019)
Nelsonia is a genus of rodent endemic to Mexican highlands with only two species: N. neotomodon (Western diminutive woodrat) and N. goldmani (GoldmanÂ´s diminutive woodrat). These species are taxonomically interesting because the few internal and external morphological differences were reported between them. Unfortunately, the scarcity of specimens and preserved internal organs available of these species limits the information to perform taxonomic studies. Hence, the objective of this study was to describe the reproductive structures in one specimen of N. goldmani collected in the biogeographic region known as Transmexican Volcanic Belt, located in the highlands of the central Mexico. We describe the external structures of the phallus and take nine measurements. The baculum was measured and described after using the classical methodology to clear, stain and preserve the whole phallus. The spermatozoa and inner testes were described using light microscopy, scanning electron microscopy, and histological techniques. Testicular volume was 319.64 mm3 and 1.34% of gonad somatic index. The phallus was relatively simple externally, laterally cylindrical, and dorsally resembling an elongated bottleneck. The baculum is an osseous structure with a cartilaginous part in its distal section. The sperm has a total mean length of 182.58 Âµm with an asymmetric head, a slight depression in its base and a large recurved hook. The histological analysis of testes indicated active spermatogenesis. We found important differences in the features and form of the phallic and baculum between N. neotomodon and N. goldmani. In N. goldmani some phallic forms were different, and some features measurements were greater than N. neotomodon. The external structures and the internal position of the baculum differ between the two species. In addition, the sperm size in N. goldmani was greater than other rodents, even those of larger corporal size like some species phylogenetically close as Neotoma genus.